Evaluation of thermal and chemical treatments on granular activated carbon to remove organic molecules from water. - Sáenz Alanís, Carina Agjaetp (2016)
The influence of three different treatments on the physical and chemical properties of activated carbon, as well as the adsorption capacity towards phenol, methylene blue and congo red was evaluated. After the heat treatment, Surface area decreased and total pore volume diminished about 8.5%, and the total basic groups decreased 18% while the total acid groups increased 8% in comparison with the raw activated carbon. Equilibrium adsorption of phenol was described well with the Freundlich model, whereas methylene blue and congo red adsorption fitted the Langmuir isotherm model. Adsorption kinetics of all three was predicted adequately with the empirical pseudo--second order model, the intraparticle diffusion model and the homogeneous solid diffusion model, but mass transfer coefficients of the diffusion models help to better understand the adsorption phenomenon. Intraparticle diffusion seems to be the rate—controlling step in the adsorption process. In conclusion, physical and chemical features of the activated carbon are affected when the adsorbent is heated under inert atmosphere increasing the adsorption capacity of phenol, methylene blue and congo red.